On computing the input to a discretized linear system - San Juan, Christian B. (Philippine Engineering Journal)
In some applications, there is the need to compute for the input signals of a linear system knowing the form of the output signal. This is normally true in physiological and mechanical systems, especially in the field of robotics. A simple way to do this is by discretizing the state equation. The resulting equations are not only easy to manipulate but also amenable to computer solutions.